Strengthening the academic curriculum for teaching public administration in the Philippines building institutional capacities to attain the millennium development goals. - Mangahas, Joel V.
That public administration education must play a key role to meet the Millennium Development Goals (MDGs) in the Philippines is the central argument of the this article. It argues that since the general program of action articulated in MDGs is grounded on the successful implementation of administration and governance reforms, it is only necessary for the MDGs to be formally introduced to the teaching and learning processes of schools of public administration in the country. Consequently, the article seeks to suggest what Philippine public administration schools can and should do support actions related to MDGs. It also aims to examine how the academic curricula for teaching public administration may be strengthened to develop competencies for institutional and organizational development towards the achievement of MDGs.
Keywords: Public administration--Study and teaching; Public administration--Curriculum; Millennium Development Goals